Penerapan Regresi Logistik Biner untuk Menganalisis Determinan Status Stunting Pada Balita di Provinsi Sulawesi Tengah Tahun 2018 - Pamungkas, Eross Wahyu; Muchlisoh, Siti (Politeknik Statistika STIS, 2023)
Stunting is still a nutritional problem experienced in several provinces in Indonesia. Central Sulawesi is one of the provinces in Indonesia with a stunting prevalence above the national rate. The stunting prevalence of Central Sulawesi Province in 2018 was 32.3 percent. This figure is still far from the World Health Organization standard, which is 20 percent for low category stunting. In the period 2018-2021, the decline in the prevalence of stunting among children under five in Central Sulawesi Province also tends to be slow compared to other provinces. In addition, the distribution of stunting in Central Sulawesi Province based on districts and cities also varies. This study aims to determine the determinants of stunting in toddlers in Central Sulawesi Province in 2018 using Riskesdas data. The method used in this study is binary logistic regression. The results of this study are, father's education, mother's education, and SEZ status in mothers have a significant effect on the stunting status of toddlers. Therefore, the government needs to optimize the 12-year compulsory education program, and pay attention to maternal health by improving existing health facilities.